2010
DOI: 10.1186/1750-1172-5-32
|View full text |Cite
|
Sign up to set email alerts
|

In Lysinuric Protein Intolerance system y+L activity is defective in monocytes and in GM-CSF-differentiated macrophages

Abstract: BackgroundIn the recessive aminoaciduria Lysinuric Protein Intolerance (LPI), mutations of SLC7A7/y+LAT1 impair system y+L transport activity for cationic amino acids. A severe complication of LPI is a form of Pulmonary Alveolar Proteinosis (PAP), in which alveolar spaces are filled with lipoproteinaceous material because of the impaired surfactant clearance by resident macrophages. The pathogenesis of LPI-associated PAP remains still obscure. The present study investigates for the first time the expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 38 publications
5
57
0
2
Order By: Relevance
“…Our experiences based on two patient cases together with the case previously reported by Barilli et al (2010) suggest that inhaled rhuGM-CSF may be useful in LPIassociated pulmonary alveolar patients. In patient 1, an excellent response to therapy was observed with no compliance problems or side effects.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our experiences based on two patient cases together with the case previously reported by Barilli et al (2010) suggest that inhaled rhuGM-CSF may be useful in LPIassociated pulmonary alveolar patients. In patient 1, an excellent response to therapy was observed with no compliance problems or side effects.…”
Section: Discussionsupporting
confidence: 56%
“…Although the exact pathogenesis of PAP in LPI has been unclear, disturbances in the function and phagocytic activity of monocyte-derived macrophages have been demonstrated (Barilli et al 2010(Barilli et al , 2012Kurko et al 2015). Thus, accumulation of proteinous material into the lungs may be caused by insufficient clearance of proteins by poorly functioning alveolar macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would justify the increased availability of arginine and, consequently, an increased synthesis of nitric oxide that, in the presence of inflammatory cytokines and endotoxins, may result in progressive lung disease [83,84]. This hypothesis was confirmed in a study which reported that the transport system of y(+)LAT-1 in the BAL monocytes and alveolar macrophages from an adult with lysinuric protein intolerance and PAP is impaired [85]. Patients with lysinuric protein intolerance do not present high levels of circulating granulocyte-macrophage colony-stimulating factor (GM-CSF) autoantibodies [85,86], thus suggesting that the GM-CSF signalling pathway is unaltered in lysinuric protein intolerance.…”
Section: Disorders Of Amino Acids Transport and Metabolismmentioning
confidence: 84%
“…It has been suggested that this may have a role in the crosstalk between T lymphocytes and macrophage leading to a defect in lymphocyte cytotoxic activity that prevents the efficient removal of antigens and results in abnormal immune activation of CTLs and macrophages explaining HLH in LPI. 18,19 There have been rare case reports of HLH secondary to other inborn errors of metabolism. HLH was described in Wolman disease, a severe systemic disease manifesting in the first days of life with vomiting, diarrhea, failure to thrive, hepatosplenomegaly, jaundice, anemia, and thrombocytopenia.…”
Section: Differential Diagnosis and Further Investigationsmentioning
confidence: 99%